A high-density genetic map of cucumber derived from Specific Length Amplified Fragment sequencing (SLAF-seq) - Xu, Xuewen; Xu, Ruixue; Zhu, Biyun; Yu, Ting; Qu, Wenqin; Lu, Lu; Xu, Qiang; Qi, Xiaohua; Chen, Xuehao (Frontiers in Plant Science, 2015)
High-density genetic map provides an essential framework for accurate and efficient genome assembly and QTL fine mapping. Construction of high-density genetic maps appears more feasible since the advent of next-generation sequencing (NGS), which eases SNP discovery and high-throughput genotyping of large population. In this research, a high density genetic map of cucumber (Cucumis sativus) was successfully constructed across an F2 population by a recently developed specific length amplified fragment sequencing (SLAF-seq) method. In total, 18.69 Gb of data containing 93,460,000 paired-end reads were obtained after preprocessing. The average sequencing depth was 44.92 in the D8 (female parent), 42.16 in the Jin5-508 (male parent), and 5.01 in each progeny. 79,092 high-quality SLAFs were detected, of which 6,784 SLAFs were polymorphic, and 1,892 of the polymorphic markers met the requirements for constructing genetic map. The genetic map spanned 845.87 cM with an average genetic distance of 0.45 cM. It is a reliable linkage map for fine mapping and molecular breeding of cucumber for its high marker density and well-ordered markers.